Pattern and distribution of peripheral arterial disease in diabetic patients with critical limb ischemia (Rutherford Clinical Category 4-6) - Motsumi, Mpapho (Department of Surgery, 2016)
Background: The literature tends to support the notion that diabetic patients typically suffer from tibio-peroneal artery occlusive disease (1) (2) (11) (5) (10) (8) with relative sparing of the foot arteries (1). This study seeks to investigate the pattern and distribution of peripheral artery occlusive disease and the arterial foot arch status in diabetic patients with critical limb ischaemia Methods: This is a one year prospective study -(January 2014 to December 2014) carried out on consecutive patients seen at Groote Schuur Hospital, Vascular Department. The inclusion criteria is: diabetic patients ≥18 years of age with critical limb ischemia who had pre- and post-intervention vascular imaging. The calculated minimum sample size of 63 limbs [756 patency levels (63x12)] was needed to achieve a power of 86% to detect a difference of 0.1900 (19%) with a target significance level of 0.05 (using PASS 11 software). The equality of distribution of categories was analyzed using the One sample Chi-square test (SPSS 22) with our Null hypothesis (N0) assuming that categories occur with equal proportions. In this case categories refers to the 5 patency levels used in this study. All 12 main arteries from infra-renal aorta to crural arteries had their patency levels graded from category 1 to category 5 (widely patent to occluded). The findings were then stratified according to gender, age group ( <40 years, 40-54 years and ≥ 55 years) and risk factor combinations [ Group1 = (DM, HPT, Dyslipidemia); Group 2= (DM, HPT, dyslipidemia, exsmoker); Group 3 = (DM, HPT, dyslipidemia, smoker)]. The three risk combination groups formed the majority of our study group (79%).